2013
DOI: 10.1523/jneurosci.3825-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Top-Down Modulation of Lateral Interactions in Visual Cortex

Abstract: The primary visual cortex (V1) changes its computation according to the perceptual task being performed. We propose that this cognitive modulation results from gating of V1 intrinsic connections. To test this idea, using behavioral paradigms that engage top-down modulation of V1 contextual interactions, we recorded from chronically implanted electrode arrays in macaques. We observed task-dependent changes in interactions between V1 sites measured both by correlation between spike trains and by coherence betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
73
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 93 publications
6
73
0
Order By: Relevance
“…These effects were greatest when the feedforward drive was present but weak. However, Ramalingam et al (2013) also found that V1 cells have higher firing rates when the element to which they were selectively sensitive was part of a contour. Amplification increased with contour length, and occurred with a latency of about 100 ms following stimulus onset.…”
Section: Modulation That Synchronizes Responses To Rf Inputmentioning
confidence: 95%
See 4 more Smart Citations
“…These effects were greatest when the feedforward drive was present but weak. However, Ramalingam et al (2013) also found that V1 cells have higher firing rates when the element to which they were selectively sensitive was part of a contour. Amplification increased with contour length, and occurred with a latency of about 100 ms following stimulus onset.…”
Section: Modulation That Synchronizes Responses To Rf Inputmentioning
confidence: 95%
“…In some conditions the amplifying effects of attention occur with latencies of more than 100 msec (e.g. Li, Piech and Gilbert, 2006;Roelfsema, Lamme, and Spekreijse, 1998;Bisley and Goldberg, 2006), but when attention can be oriented appropriately prior to stimulus onset its effects can be observed in LFPs prior to stimulus onset (Ramalingam et al, 2013). They can then affect the very first spike (Gilbert and Sigman, 2007).…”
Section: Modulation That Amplifies Responses To Rf Inputmentioning
confidence: 99%
See 3 more Smart Citations